In angulo cum libello: Traces of Personal Histories in the Notebooks of the Lithuanian Jesuits - Katilienė, Irena; Jovaiša, Liudas (Senoji Lietuvos literatūra, 2019)
The paper is devoted to the biographical information contained in the personal silva rerum-type notebooks once compiled and owned by five members of the Lithuanian Province of the Society of Jesus: fathers Simon Niklewicz (c. 1571 – 1632), Nicolaus Kopeć (c. 1615 – 1658), Georgius Krapavičius (Kropowicz) (1658–1722), Franciscus Błuś (1709–1749), and Theodatus Niewiadomski (1692–1761). Short texts (or just notes) containing biographical information played only a marginal role in the notebooks; they were dominated by the transcripts of various (mostly spiritual and devotional) texts. Such predominance of more general information in the content may have been the reason for preserving (and possible reuse) of personal notebooks in the Jesuit communities after the death of their compilers.It appears, however, that scarce biographical notes in the notebooks of the Lithuanian Jesuits may provide otherwise (i. e., in the ordinary Jesuit sources) lacking personal information, e. g., about the circumstances of the ordination and the offering of the first Mass, as proved by the cases of Fathers Krapavičius and Błuś. Besides, the notebook of Fr Niklewicz contains information about health problems and travelling, and the practice of spiritual retreats is reflected in the case of Fr Niewiadomski. The notebook of Fr Błuś contains a short curriculum vitae. It reveals obscure aspects of his biography, i. e., his early life before joining the Society, his relations with his family members, and his personal health story.The notes of the Lithuanian Jesuits reveal the ties of mutual intercessional prayer and the bonds of friendship between the members of the Society. The space of social relations of a Jesuit is expanded by the specific information about the contacts with the laypeople, mainly as students or recipients of spiritual exercises. Thus personal notebooks of the Jesuits should be regarded not only as important biographical sources but, to a lesser extent, as sources relevant to social history.
Keywords: Society of Jesus; personal writings; silva rerum; biographical sources